RANCANGAN MESIN PEMOTONG ADONAN KERUPUK GETAS - Dani Ismarini; Marini; Muhammad H Amrullah; Indah R Pratiwi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Getas crackers are one of the crackers that are in great demand by the public. Getas itself is produced in two forms some are elongated, and some are round. There are still many brittle cracker processing places that produce brittle manually, so that is the basis for the idea of this "Cutting Cracker Dough Machine" being designed. In the process of designing this machine, using the design method according to VDI 2222, with the stages of planning, conceptualizing, designing, and finishing. The machine is designed to be able to cut 15 kg of getas dough 19 about minutes by using a screw system as a dough pusher and a crankshaft mechanism to cut the dough that has come out.